A Comparison of INRs Determined with a Whole Blood Prothrombin Time Device and two International Reference Preparations for Thromboplastin - van den Besselar, A. M. H. P. (Thrombosis and Haemostasis, 2000)
Oral anticoagulant therapy is usually monitored with the prothrombin time (PT) on citrate plasma samples. In recent years instruments have been developed for measurement of the PT in non-citrated whole blood. In the present study, the manufacturer’s calibration of one type of device (CoaguChek®) in terms of the international normalized ratio (INR) was evaluated by one laboratory. Three subsequent lots of test strips for the CoaguChek were investigated using blood samples from 56 coumarin-treated patients. Citrated plasma samples from the same patients were analysed with two international reference preparations for thromboplastin (IRP), i. e., rTF/95 (recombinant human) and RBT/90 (rabbit brain). There were statistically significant INR differences between CoaguChek and the international reference preparations (p <0.001), but the mean relative deviation of the INR was not greater than 0.104. Clinically relevant criteria were used to assess the agreement between the CoaguChek and the IRP results. Standard agreement ranged from 82% to 95%. It is concluded that these test strips achieved a clinically acceptable level of accuracy. Further studies of patient management with these strips are justified.
Keywords: Prothrombin time; International Normalized Ratio; oral anticoagulant control